Implementasi Model Pembelajaran Bauran pada Pembelajaran Tematik Tema 6 Merawat Tumbuhan dan Hewan - Putri, Yuni Atika; Asiyah, Asiyah; Eliya, Ixsir (Institut Agama Islam Negeri (IAIN) Curup, 2021)
the process of implementing the mixed learning model in thematic learning theme 6 caring for plants and animals at SDN 76 Bengkulu City in class II C, and to find out what are the inhibiting and supporting factors in the process of implementing the mixed learning model in thematic learning theme 6 caring for plants. And animals. The type of research descriptive qualitative approach. The process of implementing the mixed learning model has been carried out well, namely the learning process is carried out through two stages, namely face-to-face and online, there is collaboration between the two learning models, namely the collaboration stage of sharing the syntax of the mixed learning model, the assessment between the two learning models, and the support from various parties, planning, and syntax. There are also in hibiting and supporting factors in implementing thei mplementation of the mixed learning model at SDN 76 Bengkulu City, in hibiting factors such as lack of attention from parents, students who are not ready when learning, and economic factors. While the supporting factors are the support of fellow teachers, in frastructure such as wifi, and health protocol tools.